Virtual Field Trip Agroforestry: How VR-Based Agroforestry Exploration in Coban Talun Improve Analytical Thinking in Geography? - Fortuna, Nadhifa Dewi; Purwanto; Marieieva, Tetiana (CV Bumi Spasial, 2025)
Geography learning often struggles to convey the complex concepts of natural resource management because traditional methods lack the immersive depth needed to show system interactions. In agroforestry education, cultivating analytical thinking is particularly difficult because students find it nearly impossible to imagine complex management processes and the dynamic relationships between nature and human activities.This research aims to develop Agroforestry Virtual Field Trip (VFT) media in improving students' analytical thinking skills. The method used is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The evaluation includes formative evaluation and summative evaluation through one group pretest-posttest analysis and user response questionnaire using Short-UEQ instrument. The results showed that the VFT media reached a high level of validity, with scores of 96% from material experts and 90% from media experts. The intervention had a significant effect on students' analytical thinking skills, supported by a normalized gain (N-Gain) of 0.42. While the results were statistically significant (p < 0.001), which is considered a medium improvement. Student feedback was also very positive; scores for both pragmatic and hedonic quality reached the